A method of walking trajectory for biped robot based on Newton interpolation. (8th October 2022) - Shu, Yingli; Yuan, Quande; Li, Huazhong; Ke, Wende
Trajectory design of biped robot is the premise of effective walking. By analysing the kinematics characteristics of biped robot, Newton's interpolation is used to design the trajectory of insertion point when planning periodic motion and realising Zero Moment Point (ZMP) constraint. With the increase of interpolation points, the curve fitting effect is improved and it will not lead to more expensive calculation cost, which can effectively meet the real-time requirements. Simulation results show the effectiveness of the method.